An enhanced anonymous authentication protocol for wireless sensor networks. (6th October 2020) - Li, Jiping; Yu, Tong; Wu, Yunyun; Kong, Xia; Liu, Shouyin
Nowadays, wireless sensor networks (WSNs) have played important roles in a variety of areas. However, the nature of wireless communications and restricted resources make it more likely to suffer from various kinds of attacks. As to this problem, many authentication protocols have been proposed recently to secure the communications in WSNs. Among these schemes, Singh et al.'s protocol shows great novelty. Unfortunately, we find in our current research that Singh et al.'s protocol still has the vulnerabilities to stolen/lost smart card attacks, privileged-insider attacks, the session key leakage attacks, and so on. To solve these problems, we first propose an enhanced anonymous authentication protocol by using Hash function and bitwise XOR operations based on Singh et al.'s protocol. Secondly, we conduct detailed security analysis to the proposed authentication protocol, and make security-feature comparisons with related protocols. In addition, we give formal proof and security verification of the proposed protocol by using Burrows-Abadi-Needham (BAN) logic and AVISPA tool, respectively. Finally, we give performance comparisons in terms of computing costs and communicating costs, respectively. Comparative summaries demonstrate that our protocol provides more extractive features and security guarantees with little increased overheads.